The impact of wind power plant size on economic viability at the Ojstrica location - Roger, Andraž (Journal of energy technology, 2025)
Wind energy in Slovenia has not yet achieved a significant share in the energy resource mix, due primarily to the limited number of suitable locations and opposition from local communities. Nevertheless, interest in wind power plants is increasing, as they represent significant potential for utilising renewable energy sources. The paper analyses the economic viability of wind farm installation and electricity production at the proposed Ojstrica site in the Dravograd Municipality. Two scenarios were considered, involving wind turbines with capacities of 3.5 MW and 7 MW. Based on wind speed data, turbine power curves, and an electricity selling price of 75 EUR/MWh, the study calculated the maximum investment costs for each turbine type to ensure economic viability under the condition of a net present value (NPV) equal to zero. The results show that the maximum allowable investment is 5.99 million EUR for the 3.5 MW turbine and 15.60 million EUR for the 7 MW turbine.
Keywords: economic viability; ekonomska upravičenost; net present value; neto sedanja vrednost; obnovljiva energija; Ojstrica; renewable energy; vetrne turbine; wind turbines